Food Quality and Life‐History Genotype Influence Maturation and Reproductive Traits in Female Atlantic Salmon - Maamela, Katja Susanna; Asheim, Eirik Ryvoll; O'Sullivan, Ronan James; Debes, Paul Vincent; House, Andrew Herbert; Liljestrom, Petra; Prokkola, Jenni Maria; Niemela, Petri Toivo; Erkinaro, Jaakko; Mobley, Kenyon Brice; Primmer, Craig Robert (Wiley, 2025)
Age at maturity is an important life-history trait, often showing sex-specific variation, contributing to life-history diversity in many species. Atlantic salmon (Salmo salar) are an excellent model system to investigate genetic and environmental factors affecting sex-specific maturation, yet few laboratory studies have focused on females as they mature later than males, on average. Using a 4-year common-garden experiment of Atlantic salmon, we assessed the influence of diet (low-fat vs. control) and vgll3 (a candidate gene influencing maturation age) on maturation and related phenotypic traits of female Atlantic salmon derived from two second-generation hatchery populations. We found the early-maturation associated E allele to be additively associated with a higher probability of maturation. Heritability of maturation was estimated to be 0.295, with vgll3's contribution to phenotypic variance being similar to 2%. In addition, body condition measured in the spring prior to spawning influenced maturation. Body condition, in turn, was influenced by population and diet. The more northern Oulu population and the low-fat diet were associated with lower body condition compared to the more southern Neva population and the control diet. Moreover, there was an interaction between population and diet on body condition, suggesting that populations may respond differently to nutrient availability. These results broaden our understanding of the processes underlying sex- and population-specific maturation and demonstrate that genes and environment influence age at maturity in a species that displays sex-specific variation in maturation.